Is trans-race possible in an era of unsettled identities?. Issue 8 (21st June 2017) - Moran, Anthony
ABSTRACT: Brubaker's book Trans is an important intervention in debates about sexual/gender and racial/ethnic identities in a period of generalized identity unsettlement. It challenges us to think precisely about identities and social categories. Thinking with trans proves to be intellectually productive, showing us the similarities and differences between transgender and trans-race. This contribution to the book symposium raises questions about the specificity of Indigenous identities framed by settler-colonial relations. It also discusses transgender in a global context where non-Western identities have been challenged, and where non-Western protagonists have responded to cultural liberalization at times with forms of gender and sexual repression.